Bioprocess strategies for maximizing SCOBY growth and evaluating fermentation dynamics on phenolic content and antioxidant activity in Roselle-based Kombucha - Widiastuti Setyaningsih; Wa Ode Reza Sindy Warni; Intan Dewi Larasati; Rini Yanti; Tyas Utami (Phytomedicine Plus)
Roselle-based kombucha is a promising functional beverage due to its bioactive compounds, high phenolic content, and anthocyanins, which contribute to color stability, anti-inflammatory effects, and cardioprotective benefits. This study aimed to optimize fermentation parameters—roselle concentration, sucrose levels, and initial symbiotic culture of bacteria and yeast (SCOBY) mass—to enhance microbial activity, phenolic stability, and antioxidant properties.High-performance liquid chromatography (HPLC) identified chlorogenic acid (270.62 mg L⁻¹), quercetin-3-glucoside (31.96 mg L⁻¹), and rutin (7.7 mg L⁻¹) as predominant phenolics, with protocatechuic acid increasing over 14 days. Optimized fermentation conditions (5 g roselle, 12% sucrose, 25 g SCOBY) resulted in higher SCOBY growth (41.66 g) and superior bioactive stability compared to traditional tea kombucha. Fermentation significantly influenced key parameters: pH remained stable (2.16 to 2.21) due to buffering organic acids, titratable acidity increased (0.60% to 2.33%), and sucrose concentration decreased (12.0 to 10.2 °Brix). Color analysis (CIELab) revealed dynamic pigment changes, reflecting anthocyanin degradation and transformation. Storage stability tests showed that phenolic compounds remained stable at 4°C, while room-temperature storage increased phenolic content, likely due to continued microbial metabolism. Antioxidant activity assays confirmed robust antioxidant potential, with IC50 values remaining stable in cold storage: DPPH (9.71 to 9.59 mg L⁻¹), ABTS (8.68 to 7.60 mg L⁻¹), and FRAP (10.01 to 9.84 mg L⁻¹). These findings underscore roselle kombucha's potential as a scalable, nutritionally enhanced functional beverage, emphasizing its phenolic stability and antioxidant properties under optimized fermentation and storage conditions. This study provides practical insights for scaling production, improving cost-efficiency, and advancing functional beverage development.